Recovery – A Disguise of Colonization - Dobrowolski, Piotr (Porównania, 2021)
The article refers to Arkadiusz Kalin’s monograph Mit Ziem Odzyskanych w literaturze. Postkolonialny przypadek Ziemi Lubuskiej [The Myth of the Recovered Territories in Literature. The Postcolonial Case of the Lubusz Land] discussing the cultural problems relating to the political myth of the Recovered Territories and the issue of its representation in literary output. These processes are presented (and concealed) in the top-down ideological narrative of the Recovered Territories, with a significant impact on the shaping of social attitudes. The myth of Recovered Territories constituted an official and totalizing narrative, which, however, functioned within numerous variants and local policies. The accents in the ‘re-polonizing’ narrative were distributed quite differently in different regions. The example of the Lubusz Land seems to show the fundamental assumption underlying the idea of the Recovered Territories – a feature of colonization. Taking over the territories on the Lower Warta and the Central Oder rivers – that had little to do with Polishness, even that of the Piast era – required breakneck efforts to disguise the territorial, economic, and social colonization that had already begun at the end of WWII. The issue of cultural colonisation – a process of construction of Polishness of this region that displaces seven hundred years of German history – inevitably comes to the fore. Literature has therefore played an important role in the manufacturing of a regional identity in the spirit of ‘reclamation’. Kalin treats the myth of the Recovered Territories as a colonization project, equipped ideologically long before 1945 in the so-called Western thought. The very name ‘Recovered Territories’ has a pre-war origin. This term was officially used after WWII and until the beginning of the 1950s, but it took root in the social consciousness and was used until the end of the 1980s to describe the evolving political myth of ‘recovery’.